2020
DOI: 10.3390/cancers12092638
|View full text |Cite
|
Sign up to set email alerts
|

How Different Are the Molecular Mechanisms of Nodal and Distant Metastasis in Luminal A Breast Cancer?

Abstract: Lymph node status is one of the best prognostic factors in breast cancer, however, its association with distant metastasis is not straightforward. Here we compare molecular mechanisms of nodal and distant metastasis in molecular subtypes of breast cancer, with major focus on luminal A patients. We analyze a new cohort of 706 patients (MMCI_706) as well as an independent cohort of 836 primary tumors with full gene expression information (SUPERTAM_HGU133A). We evaluate the risk of distant metastasis, analyze tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 168 publications
(187 reference statements)
0
7
0
Order By: Relevance
“…For luminal A subtype, well established and effective treatment includes hormone therapy that targets estrogen and progesterone receptors and is based on tamoxifen or aromatase inhibitors [ 8 , 9 ]. However, up to 16% of node-negative luminal A patients and up to a third of lymph node positive luminal A patients at the time of diagnosis develop distant metastasis [ 10 , 11 ]. Moreover, about 20% to 30% of patients with estrogen receptor-positive tumors become resistant to the endocrine treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For luminal A subtype, well established and effective treatment includes hormone therapy that targets estrogen and progesterone receptors and is based on tamoxifen or aromatase inhibitors [ 8 , 9 ]. However, up to 16% of node-negative luminal A patients and up to a third of lymph node positive luminal A patients at the time of diagnosis develop distant metastasis [ 10 , 11 ]. Moreover, about 20% to 30% of patients with estrogen receptor-positive tumors become resistant to the endocrine treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the NF-κB is best known as a key regulator of inflammation and immune response ( 83 , 84 , 85 ), we indeed detected rearrangement of protein complexes involved in NF-κB signaling, innate immune response, antigen presentation, and IL-1 pathways. However, other studies demonstrated NF-κB pathway to support cancer development and progression, including lymph node metastasis of luminal A breast tumors ( 16 , 17 ), as it contributes to number of other cellular processes and promotes cellular growth and proliferation ( 86 , 87 , 88 ). We demonstrated the effects of NF-κB activity on composition of protein complexes associated with regulation of cell cycle and Wnt pathway that represents an important therapeutic target in breast cancer ( 89 , 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, former studies linked aberrant activity of NF-κB with cancer, including enhanced expression of NF-κB factors in breast cancer cells as well as their participation in breast tumorigenesis ( 9 , 11 , 12 , 13 , 14 , 15 ). Our previous studies ( 16 , 17 ) identified association between increased transcript and protein NF-κB levels and lymph node metastasis of luminal A breast tumors. Inhibition of NF-κB thus hypothetically represents a potential anti-metastatic therapeutic strategy for this group of tumors.…”
mentioning
confidence: 93%
“…While nodal status was predictive of systemic metastasis, patients with negative nodal status could still have systemic metastasis [ 31 ]. Conversely, not all patients with positive nodal status would have systemic metastasis; hence, the relationship between nodal status and systemic metastasis is not unequivocal [ 32 ]. It was reported that about one-third of breast cancer patients with a negative nodal status could still develop systemic metastasis, while one-third of breast cancer patients with a positive nodal status do not develop systemic metastasis at all [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, not all patients with positive nodal status would have systemic metastasis; hence, the relationship between nodal status and systemic metastasis is not unequivocal [ 32 ]. It was reported that about one-third of breast cancer patients with a negative nodal status could still develop systemic metastasis, while one-third of breast cancer patients with a positive nodal status do not develop systemic metastasis at all [ 32 ]. Despite this, nodal status remained the most predictive factor for systemic metastasis at staging in our study.…”
Section: Discussionmentioning
confidence: 99%